Kontekstualisasi Surah Al-Mulk Ayat 14 terhadap Pengawasan Berbantuan CCTV untuk Pembentukan Karakter di Pesantren Tahfiz Anak - Taufikin Taufikin; Habib Badawi; Makmur Harun (Islamic Religious Education Departement, 2026)
education; however, the dynamics of student life in the digital era present new challenges in maintaining behavioral consistency, whether under direct supervision or otherwise. This study aims to analyze how the use of Closed-Circuit Television (CCTV) is interpreted as a tool for character education by contextualizing Surah Al-Mulk, verse 14, regarding Allah's All-Knowing nature concerning all human actions. A qualitative method with a case study design was employed at a pesantren focused on Quranic memorization (tahfiz) for children. Data were gathered through observation, in-depth interviews with caregivers, teachers, administrators, and students, and analysis of institutional documents. Analysis was conducted using a thematic analysis codebook involving a staged coding process, theme development, and source triangulation. The results indicate that CCTV is not perceived merely as an instrument of control but as a pedagogical medium that helps bridge external surveillance with the cultivation of internal awareness (muraqabah). The findings also reveal that the effectiveness of CCTV relies on the internalization of religious values ​​through guidance, role modeling, and spiritual reflection; consequently, student compliance transcends the mere feeling of being watched and evolves into a sustained moral consciousness. This study contributes to a broader understanding of surveillance technology implementation in Islamic education by demonstrating that the pedagogical function of CCTV becomes more meaningful when positioned as a tool supporting the internalization of Quranic values, rather than as a standalone control mechanism.